Economic Growth in the Special Region of Yogyakarta from 2013 to 2020: The Impact of DAU, DAK, and PAD - Aditya Cahya Nugraha; Eni Setyowati (Ekonomis: Journal of Economics and Business, 2023)
The aim of this research is to demonstrate how the Yogyakarta Special Region's DAU, DAK, and PAD will affect economic growth from 2013 to 2020. The quantitative technique of this study employed a multiple linear regression analysis to ascertain the association between the DAU, DAK, and PAD variables and economic growth in the Special Region of Yogyakarta. The population of the research was the City/Regency in the Special Region of Yogyakarta in the years 2013 to 2020. The results of this analysis show that DAU will negatively affect Yogyakarta's Special Region's economic growth between 2013 to 2020. Between 2013 to 2020, Yogyakarta's Special Region's economy grew favorably as a result of DAK and PAD.